Pancasila Village Tolerance Character Education Model: A Case Study of SDN 1 Balun Lamongan - Lailatul Muharromah; Akhwani Akhwani; Sukron Djazilan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
This study examines the model of tolerance character education in Pancasila Village, a case study at SDN I Balun, Lamongan Regency. Balun Village is known as the